AB0632 MAINTENANCE RITUXIMAB IN ANCA ASSOCIATED VASCULITIS – OBSERVATIONAL DATA FROM UNIVERSITY HOSPITAL COVENTRY, UK. (June 2019) - Rutter, Megan; Dubey, Shirish; Short, Andrew
Abstract : Background: Rituximab is considered an effective 1 maintenance therapy in anti-neutrophil cytoplasmic antibody (ANCA) associated vasculitis (AAV), with reduced relapse rates post induction therapy and comparable adverse event profile to other agents such as azathioprine 2 . Objectives: To describe the clinical outcomes of all patients receiving maintenance Rituximab for aAV in University Hospital Coventry in UK. Methods: Records from the Renal and Rheumatology units were used to identify patients receiving maintenance Rituximab. Electronic patient records (EPR) were used to collate laboratory and clinical data. Results: We identified 38 patients, with the diagnosis of aAV made 11 months to 19 years previously. 16 (42%) had been diagnosed within the last five years. Age range was 19-87 years old with roughly half (21; 54%) being male. Maintenance Rituximab was started between January 2010 and September 2018. Most patients received a fixed 6 monthly protocol. Seven patients (18%) died within the observation period. More details in table 1 below. Conclusion: The effectiveness of Rituximab as a maintenance therapy in aAV is borne out by this real world data, with 31/38 patients demonstrating full clinical response. Longer term treatment and low grade disease continue to be issues as evidence for optimal management strategies is lacking. Infections, including severe infections necessitating admission, were common. PR3 positive patients are over-represented, in keeping with the known higher rate of relapse. References: [1] Smith, Rona M., et al. "Rituximab for remission maintenance in relapsing antineutrophil cytoplasmic antibody–associated vasculitis." arthritis & Rheumatism 64.11 (2012): 3760-3769. [2] Guillevin, Loïc, et al. "Rituximab versus azathioprine for maintenance in aNCA-associated vasculitis." New England Journal of Medicine 371.19 (2014): 1771-1780. I confirm that the abstract fulfils the requirements for a late breaking submission and that the research results were not available at the time of the original deadline (31 January 2019) Yes Disclosure of interests: Megan Rutter: None declared, Shirish Dubey Grant/research support from: Roche provided a grant 5 years ago, Speakers bureau: Yes, BMS and internis, andrew Short: None declared